Ultrafast response humidity sensors based on polyvinyl chloride/graphene oxide nanocomposites for intelligent food packaging - Moustafa, Hesham; Morsy, Mohamed; Ateia, Mahmoud A.; Abdel-Haleem, Fatehy M. (Sensors and actuators. A. Physical., 2021)
[Display omitted] •Ultrafast response humidity sensors based plasticized PVC/GO nanofilms were successfully fabricated by In-situ route.•AFM and Raman images showed a better dispersion of GO NPs for sensors 1 & 3.•The mechanical and thermo-stability properties of fabricated sensors were enhanced.•RH sensor 3 is the optimum and possesses high sensitivity and response/recovery time (i.e. 4/6 s).•These sensors have excellent possibility for use in intelligent food packaging. Fabricating high response humidity sensors can create new-fashioned applications and avenues for stakeholder interaction. Thus, this paper addresses an efficient fabrication route based on consolidated graphene oxide (GO) nanoplatelets inside the polyvinyl chloride (PVC) in presence tricresyl phosphate (TCP) plasticizer by In-situ method. The structure of synthesized GO was verified by X-ray diffraction (XRD) and Fourier transform infrared imaging microscopic analysis (FT-IR-IM). Three different proportions of GO (i.e., 1, 3 and 6 wt.%) were used to fabricate plasticized PVC sensors. The morphology of sensors was investigated by atomic force microscopy (AFM) and transmission electron microscopy (TEM) techniques. The AFM & TEM images showed that better dispersion of GO nanoplatelets in the PPVC matrix occurred at 1 and 3 wt.%. Furthermore, other measurements such as Raman spectroscopy, mechanical properties and thermogravimetric analysis (TGA) were conducted on the fabricated PVC sensors. Also, the humidity sensing properties were tested in a wide range of relative humidity (11–85 % RH) and frequency (100 Hz–100 kHz). The data manifested that the optimum measuring frequency was 1 kHz. Moreover, the obtained results from humidity sensing at 1 kHz exhibited that sensor 3 (PPVC/GO-3%) possessed higher sensitivity, lower hysteresis with ultrafast response speed (∼ 4 s) and recovery time (∼ 6 s) compared to other sensors. This result reveals excellent possibility of using sensor 3 as humidity sensing for intelligent food packaging and other practical applications.